2020
DOI: 10.1007/s10346-019-01325-1
|View full text |Cite
|
Sign up to set email alerts
|

An extreme May 2018 debris flood case study in northern Slovenia: analysis, modelling, and mitigation

Abstract: Debris floods can cause large economic damage and endanger human lives. This paper presents an extreme May 2018 debris flood that occurred in northern Slovenia near the Krvavec ski resort and caused large economic damage. The debris flood was initiated by an extreme rainfall event with a return period of over 50 years. There were large differences in the measured rainfall amounts using different equipment. The estimated volume of the debris material during the event was 4000 m 3 /km 2 for the Brezovški graben.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Степента на природната опасност се определя от геоложки (наличие на кластичен материал и фактори, водещи до акумулирането му), геоморфоложки (характер на водосборите) и климатични фактори. Разработени и тествани са методики за оценка на различните фактори (Theule et al, 2012;Kadetova et al, 2016;Mazzorana et al, 2020) в различни обстановки (Wilford et al, 2005;Sepúlveda et al, 2015;Jakob et al, 2016;Bezak et al, 2020). Според дефиницията на NRC (1996) конусът на р. Глазне се характеризира като активен.…”
Section: природни опасностиunclassified
“…Степента на природната опасност се определя от геоложки (наличие на кластичен материал и фактори, водещи до акумулирането му), геоморфоложки (характер на водосборите) и климатични фактори. Разработени и тествани са методики за оценка на различните фактори (Theule et al, 2012;Kadetova et al, 2016;Mazzorana et al, 2020) в различни обстановки (Wilford et al, 2005;Sepúlveda et al, 2015;Jakob et al, 2016;Bezak et al, 2020). Според дефиницията на NRC (1996) конусът на р. Глазне се характеризира като активен.…”
Section: природни опасностиunclassified
“…The RAMMS model was calibrated using the extreme May 2018 debris flood in Brezovški and Lukenjski graben torrents below the Krvavec ski area close to the City of Ljubljana (Bezak et al, 2020). The estimated magnitude of the May 2018 flood was 4,000 m 3 .…”
Section: One-and Two-dimensional Numerical Modelling Of Debris Flowsmentioning
confidence: 99%
“…Check dams are an effective soil and water conservation engineering measure for trapping sediment and mitigating soil erosion effects and have been used worldwide (Abbasi et al, 2019). Check dams are constructed in gullied channels to mitigate flood damage (Bezak et al, 2020), control sediment transport (Shi et al, 2019), stabilize slopes and torrential channels (Piton & Recking, 2017), enhance carbon storage and sequestration (Mongil-Manso et al, 2019) and serve as high-quality croplands when filled with sediment (Jin et al, 2012). Wang et al (2011) reported that >100 000 check dams had been built on the Loess Plateau in the last 50 years.…”
Section: Introductionmentioning
confidence: 99%